SAT0561 METATARSOPHALANGEAL JOINT MEDIAL COLLATERAL LIGAMENT MEASUREMENT, A NOVEL ULTRASOUND FEATURE OF MONOSODIUM URATE DEPOSITION IN THE JOINT. (2nd June 2020) - Flood, R.; Kane, D.; Mullan, R.
Abstract : Background: Acute gouty arthritis most commonly initially affects the first metatarsophalangeal joint (MT1). (1) Musculoskeletal ultrasound (US) is a reliable tool for detecting monosodium urate crystal (MSU) deposition in gout and hyperuricemia with validated, ultrasound features of double contour (DC) sign, tophus, and erosions. (2, 3) The collateral ligaments of MT1, which originate on the medial and lateral epicondyles of the metatarsals and extend to the proximal phalanx, function to stabilize the joint. (4) While tophus deposition typically occurs between the medial collateral ligament (MCL) and head of MT1, small MSU aggregates may be indistinguishable from surrounding tissue. In this study using US, we propose that an increased vertical depth between the superficial surface of the MCL to cortical surface of MT1 (dMC-MT) is indicative of MSU deposition (see figure 1 ). The aim was to evaluate associations of dMC-MT with serum uric-acid level (sUA) in a cohort of individuals with hyperuricaemia and non-episodic foot pain. We propose a novel sonographic feature of MSU crystal deposition in the MT joint. Objectives: 1.)To evaluate the association between sUA and dMC-MT 2.)To record the presence/absence of classical features of MSU deposition including; double contour sign, erosions and tophi in a cohort of patients with hyperuricaemia and foot pain. 3.)To evaluate the associations between sUA and dMC-MT in those withclassical features of MSU deposition (DC, erosion, tophi). Methods: Following informed consent, hyperuricaemic patients (n = 52) underwent bilateral US of the 1MT using LogiqE9 at 15 MHz. Features of MSU deposition including DC sign, tophus and juxta-articular erosion were recorded. The dMC-MT was measured as the mean of the perpendicular distance between the superficial surface of the midpoint of the MCL to the MT1 head. Statistical analysis was performed using SPSS V.25 software. Data presented as MEAN ± S.E unless otherwise indicated. Results: DC sign, tophus and erosion occurred in 31%, 20.7% and 19% of cases, respectively. Mean sUA was higher in tophus positive (540 ± 36) versus non tophus (470 ± 16) (p<0.01) and erosion positive (522 ± 32) versus non erosion (477± 17) patients. dMC-MT was significantly greater in tophus positive patients (0.34cm ± 0.17cm) versus non tophus (0.27cm ± 0.01cm) (p < 0.01). dMC-MT was significantly greater in erosion positive patients (0.31cm ± 0.18cm) versus non erosion (0.28cm +0.01cm) (p < 0.05). In DC negative patients dMC-MT was significantly correlated with increasing sUA (r = 0.34 p = <0.05). No correction between dMC-MT and sUA was seen in DC positive patients. Conclusion: dMC-MT is significantly greater both in patients with tophus and erosions indicating its role as an additional marker of MSU crystal deposition. Furthermore a significant association between dMC-MT and sUA in DC negative patients suggests that dMC-MT may be a more sensitive indicator of early urate deposition in a subset of patients where the earliest site of urate deposition has not occurred directly on to articular hyaline cartilage. dMC-MT may therefore be a sensitive tool for very early urate deposition. Further studies clarifying a role for dMC-MT are now required. References: [1]Wallace SL, Robinson H, Masi AT, Decker JL, Mccarty DJ, Yü T -f. Preliminary criteria for the classification of the acute arthritis of primary gout. Arthritis Rheum. 1977;20(3):895–900. [2]Howard RG, Pillinger MH, Gyftopoulos S, Thiele RG, Swearingen CJ, Samuels J. Reproducibility of musculoskeletal ultrasound for determining monosodium urate deposition: Concordance between readers. Arthritis Care Res. 2011;63(10):1456–62. [3]Stewart S, Dalbeth N, Vandal AC, Rome K. Characteristics of the first metatarsophalangeal joint in gout and asymptomatic hyperuricaemia: A cross-sectional observational study. J Foot Ankle Res. 2015;8(1):1–8. [4]Finney FT, Cata E, Holmes JR, Talusan PG. Anatomy and Physiology of the Lesser Metatarsophalangeal Joints. Foot Ankle Clin. 2018;23(1):1–7. Disclosure of Interests: None declared